2022
DOI: 10.3126/jonmc.v11i1.45720
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Clinical Study for Safety and Efficacy of Intralesional Tuberculin Purified Protein Derivative in Treatment of Palmoplantar Verruca

Abstract: Background: Multiple treatment options are available for verruca, however none is completely effective. Conventional modalities such as salicylic acid, cryotherapy have inconsistent treatment efficacies. Newer modalities such as immunotherapy, bleomycin and lasers have shown higher clearance rates of warts in recent studies. Immunotherapy is an innovative approach to treat warts which relies on the principle of enhancement of cell-mediated immunity. This study was done to evaluate the efficacy of immunotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In this study, patients received an intralesional injection of 0.1 mL PPD into the most prominent wart every two weeks, with a maximum of 6 sessions. 14 In a study by Nimbalkar et al, abscess and localized hair loss at the injection site were noted in 1 patient each. Patients in this study received PPD-10TU injected intralesionally into the most prominent wart every two weeks for a maximum of 6 sessions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this study, patients received an intralesional injection of 0.1 mL PPD into the most prominent wart every two weeks, with a maximum of 6 sessions. 14 In a study by Nimbalkar et al, abscess and localized hair loss at the injection site were noted in 1 patient each. Patients in this study received PPD-10TU injected intralesionally into the most prominent wart every two weeks for a maximum of 6 sessions.…”
Section: Discussionmentioning
confidence: 94%
“…6 sessions 50 0 3 Pain, edema Milante et al 40 2019 (Philip-pines) Randomized, open-label, superiority trial Single injection PPD (1) Multiple injection PPD (2) 1: 29 2: 29 Simple, recalcitrant; common Test dose: 0.1 mL PPD-5TU, intradermal on forearm Group 1: PPD-5TU, volume injected determined by by the size of skin test reactivity according to Kus et al 13 intralesion on largest wart Group 2: PPD–5TU, intralesion on all lesions, volume injected determined as maximum 88 TU or 1.76 mL 2-weeks interval, max. 6 sessions 1: 58.6 2: 79.3 0 in all groups 6 1: pain, fever, malaise, edema, pain 2: fever, malaise, edema, vesiculation, more painful than group 1 Mishra et al 14 2022 (Nepal) Open label study PPD 54 Simple, recalcitrant; palmo-plantar, periungual 0.01 mL PPD, intralesion on the largest wart 2-weeks interval, max. 6 sessions 66.7 11 3 2 cases of local site reaction: intense swelling, pain, and edema requiring therapy discon-tinuation Other: mild erythema, edema, pain Moham-med et al 41 2020 (Egypt) RCT PPD (A) MMR (B) Saline (C) A: 30 B: 30 C: 30 Recalcitrant; common, plane, plantar, periungual, ano-genital Test dose: PPD 0.1 mL or MMR 0.1 mL, intradermal on forearm Group A: 0.2 mL PPD (10 TU), intralesion on largest wart Group B: 0.2 mL MMR (20 IU), intralesion on largest wart Group C: 0.2 mL saline, intralesion on largest wart 2-weeks interval, max.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 In immunotherapy, the injection of antigen to which the patient was previously sensitized induced the elicitation phase of the immune response to recognize HPV antigens. 34 Although the previous vaccination status was not confirmed, evidence showed that the https://doi.org/10.2147/IMCRJ.S426665…”
Section: Discussionmentioning
confidence: 99%